A pertinent approach: Two class of uncertain priority queuing models under the steady state condition - Pamučar Dragan; Lakshmanaraj Ramya; Samayan Narayanamoorthy (Yugoslav Journal of Operations Research)
The main purpose of this research article is to provide an appropriate interpretation of the priority queuing model. It creates uncertain sequence models with priority discipline, non-priority systems, models with priority systems, and models with non-priority systems. Here, we propose two models. First, we discussed one array with a server and the second, two arrays with a server. These two model customers follow the rule of first come first served in their queue. The presence and service process follows the Poisson process and the high-speed process with ambiguous parameters. Our results are responsible for the best choice of exchange of preferred discipline. Blurred sequence models are more appropriate than uncertain scenes, which are commonly used as part of reality. Numerical results are provided to deal with the current service discipline. Despite the challenge of determining the optimal single-server uncertain queuing model with two class-priority fields, the steady-state performance of the service process is evaluated.